“We are not ready for this”: physicians’ perceptions on climate change information and adaptation strategies - qualitative study in Portugal - Ponte, Nidia; Alves, Fátima; Vidal, Diogo Guedes (Frontiers in Public Health, 2024)
BackgroundClimate change presents several challenges to public health and its professionals. This article aims to fill a significant gap in the current literature by understanding physicians’ perceptions of their role in educating others about health adaptation to climate change. It also explores their knowledge of health policies related to this issue in Portugal and their perceived influence on the development of adaptation policies at both local and national levels within the health sector.MethodsTo this end, we applied a qualitative and case study approach, interviewing 13 physicians in Portugal, including general practitioners and specialists. The data was collected using a semi-structured interview script, and a content analysis was performed to categorize the responses and gain a comprehensive understanding of the phenomenon.ResultsThe main results of this study highlight the need for a more systematic approach to training physicians, including the relationship between climate change and health. Concerning policies, this research highlights the need for more consistent communication and precise guidelines for dealing with the impacts of climate change on public health.ConclusionAs the first exploratory study focusing on Portuguese physicians, this research provides unique insights into their views on the potential to influence patient behavior and health policy. Importantly, it offers valuable recommendations for health policy strategies, particularly in awareness-raising and training plans for these professionals, thereby demonstrating the research’s practical implications.